MiR5651, miR170-3p, and miR171a-3p Regulate Cadmium Tolerance by Targeting MSH2 in Arabidopsis thaliana - Xianpeng Wang; Hetong Wang; Xiuru Sun; Zihan Tang; Zhouli Liu; Richard A. Ludlow; Min Zhang; Qijiang Cao; Wan Liu; Qiang Zhao (Plants)
The DNA mismatch repair (MMR) system plays a crucial role in repairing DNA damage and regulating cell cycle arrest induced by cadmium (Cd) stress. To elucidate the mechanism by which miRNAs target AtMSH2 in regulating Arabidopsis’ response to Cd stress, the wild-type Arabidopsis, Atmsh2 mutant, and three miRNA-overexpressing transgenic lines were grown hydroponically in half-strength MS solution containing cadmium (Cd) at concentrations of 0, 0.5, 1, 2, and 3 mg/L for 5 days. miRNA-seq analysis, bioinformatics prediction, dual-luciferase reporter assays, and qRT-PCR results demonstrated that miR5651, miR170-3p, and miR171a-3p specifically targeted AtMSH2 and their expression levels showed a significant negative correlation. Compared to wild-type (WT) Arabidopsis, Cd stress tolerance was significantly enhanced in miRNA-overexpressing transgenic lines. Moreover, exogenous application of these three miRNAs in half-strength MS liquid medium also markedly improved Cd stress tolerance in wild-type Arabidopsis. Furthermore, the expression of these three miRNAs expression was further upregulated by Cd stress in a dose-dependent manner. Additionally, DNA damage response in miRNA-overexpressing transgenic lines was promoted based on the expression of DNA repair, DNA damage signaling, and cell cycle genes, which differed from both wild-type and Atmsh2 plants. Taken together, miR5651, miR170-3p, and miR171a-3p participated in Cd stress response and improved plant Cd tolerance by mediating the expression of AtMSH2. Our study provides novel insights into the epigenetic mechanisms of Cd tolerance in plants, which sheds light on breeding for stress resilience in phytoremediation.